No longer an untreatable disease: How targeted and immunotherapies have changed the management of melanoma patients. Issue 6 (15th August 2014) - Girotti, Maria Romina; Saturno, Grazia; Lorigan, Paul; Marais, Richard
Abstract : The discovery that BRAF is a driver oncogene in cancer, and complementary improvements in our understanding of the immune system have resulted in new targeted and immune‐therapies for metastatic melanoma. Targeted therapies achieve impressive clinical results in carefully selected patients but the development of resistance seems inevitable in most cases. Conversely, immune‐checkpoints inhibitors can achieve long‐term remission and cures, but in a smaller proportion of patients, and biomarkers to predict which patients will respond are not available. Nevertheless, melanoma has led the evolution of cancer treatment from relatively nonspecific cytotoxic agents to highly selective therapies and here we review the lessons from this paradigm shift in treatment and the opportunities for further improvements in outcomes for melanoma patients.